New Perspectives on the Role of Frontier Molecular Orbitals in the Study of Chemical Reactivity: A Review - Pereira, D. H.; La Porta, F. A. [UNESP]; Santiago, R. T.; Garcia, D. R.; Ramalho, T. C. (Brazilian Chemical Soc, 2016)
Molecular orbitals play a crucial role in the understanding of the chemical reactivity at the atomic level and are important descriptors for the rationalization of various chemical reactions. In this context, the molecular orbital concept stated by Fukui refers to the use of the frontier electron density, HOMO e LUMO, for predicting the most reactive position on chemical species: HOMO (highest occupied molecular orbital energy) and LUMO (unoccupied molecular orbital of lowest energy). However, the HOMO-LUMO approach has some limitations, and other concepts are needed to complement the HOMO-LUMO arguments. New perspectives on the chemical reactivity of organic and inorganic compounds can, easily, be rationalized in terms of the composition and location of the frontier molecular orbitals. Thus, in this review, we have analyzed our recent efforts to investigate the role of the Frontier Effective-for-Reaction Molecular, so-called FERMO, which emerged more recently as a powerful tool to describe the breaking and formation of new chemical bonds and, thus open new possibilities to better understand the mechanistic aspects that govern chemical reactivity of atoms and molecules.
Keywords: FMO; FERMO; HOMO-LUMO; theoretical calculations and reactivity